Analysis of the spatial-temporal distribution characteristics of hepatitis E in Jiangsu province from 2005 to 2020 - Shi, Yao; Shen, Wenqi; Liu, Wendong; Zhang, Xuefeng; Shang, Qingxiang; Cheng, Xiaoqing; Bao, Changjun (Frontiers in Public Health, 2023)
Objective: This study attempts to analyze the spatial clustering and spatial-temporal distribution characteristics of hepatitis E (HE) at the county (city, district) level in Jiangsu Province, to provide a scientific basis for the prevention and control of HE.The information on HE cases reported in the Chinese Center for Disease Control and Prevention Information System from 2005 to 2020 were collected for spatial autocorrelation analysis and spatial-temporal clustering analysis.From 2005 to 2020, a total of 48,456 HE cases were reported in Jiangsu Province, with an average annual incidence rate of 3.87/100,000. Male cases outnumbered female cases (2.46:1), and the incidence was highest in the 30-70 age group (80.50%). Farmers accounted for more than half of all cases (59.86%), and the top three cities in terms of average annual incidence were all in Zhenjiang City. Spatial autocorrelation analysis showed that the Global Moran's I of HE incidence varied from 0.232 to 0.513 for the years. From 2005 to 2020, 31 counties (cities, districts) had high and statistically significant HE incidence, and two clustering areas were detected by spatial-temporal scanning.HE incidence in Jiangsu Province from 2005 to 2020 was stable, with age and gender differences, regional clustering, and spatial-temporal clustering. Further investigation of HE clustering areas is necessary to formulate corresponding targeted prevention and control measures.